PEMANFAATAN LIMBAH CANGKANG KERANG SEBAGAI PAKAN TERNAK BERKUALITAS DI DESA TAMBAK CEMANDI SIDOARJO - Qurrota A’yuni; Atik Widiyanti; Ika Fitri Ulfindrayani; Yanuar Risah Prayogi; Sonhaji Arif; Anggun Fitria Laila Ningsih (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Tambak Cemandi Village is an area located in the coastal area of Sidoarjo Regency because it is the easternmost region and is directly adjacent to the Java Sea. The geographical location adjacent to sea water is a benefit for the people of Tambak Cemandi Village to look for livelihoods as fishermen. In their work, fishermen are divided into several activities, there are those who go out to sea to fish and some who dive specifically to look for shellfish. The shells meat is taken for further processing, while the clamshell is thrown away. This causes the accumulation of shells waste around the residential areas so that makes a dirty views and a negative impact on the health of residents and the surrounding environment. Some steps have been taken to reduce the waste, among others, as a backfilling of the street yard, but when the rainy season comes, a pile of shell produces an unpleasant odor that invites swarms of rats and insects that can cause various digestive diseases. In addition, this thing also has a negative impact on the planned formation of the Sidoarjo coastal area into a fishing tourism area and river comb tourism. On the other hand, the shell contain high calcium so that they can be used as animal feed. One of the community service agendas carried out to overcome the problem of shell waste is to use it as animal feed ingredients. In this case, the type of poultry such as layer hens, layer ducks and broilers. The approach method used is training and workshop on processing shells to become ready-to-eat animal feed.